Winning meetings and events for your venue - Davidson, Rob; Hade, Anthony (Oxford Goodfellow Publishers Ltd, 2014)
Meetings and events are a major source of revenue for the venues that host them. But competition to win meetings and events is growing fast as new venues, large and small, are opening up all over the world and existing venues are expanding, refurbishing and modernizing their offer in order to increase their share of this lucrative market. However busy sales and marketing staff often struggle to implement and keep up to date with the many tools and techniques that can help them bring business to their venues. New staff in particular often feel the need for a structured, comprehensive guide to sources of business for their venues as well as detailed instruction on the most effective ways of winning meetings and events to fill their meeting spaces and create loyal customers. This book focuses directly on these issues. It provides a clear and comprehensive guide to the wide range of techniques required by sales and marketing staff to effectively win meetings and events business for their venue
The structure of the meetings and events industry -- Sources of business -- Developing relationships with clients -- Working with intermediaries -- Site inspections -- Winning new business at exhibitions -- The changing market environment -- Appendix : International associations of interest to venue sales professionals.
Includes bibliographical references and index.
Keywords: Special events -- Management; Special events -- Marketing.Travel.; Special events -- Planning